2023
DOI: 10.1007/s11250-023-03460-3
|View full text |Cite
|
Sign up to set email alerts
|

Pumpkin seed oil–supplemented diets promoted the growth productivity, antioxidative capacity, and immune response in heat-stressed growing rabbits

Abstract: Heat stress is the most major environmental element contributing to rabbit health problems and reduced production. It is proposed that essential oils be applied to alleviate heat stress-induced oxidative damage in rabbits. The purpose of this feeding trial was to determine the protective impact of pumpkin seed essential oil (PSO)–supplemented diets in reducing the threat of unambient temperature on growing rabbits. Five groups of 5-week-old rabbits were allocated randomly into separated galvanized wire battery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…Regarding PSO Ragab et al, (2013b) reported that the concentrations of thyroxin (T 4 ) and triiodothyronine (T 3 ) hormones were higher in groups supplemented by PSO in rabbits which might be related to vitamin E and a phenolic compound found in PSO which has antioxidant properties by removing free radicals and inhibiting fat peroxidation and thus preserving the cell membrane of thyroid gland. Contradicted results were reported by Abdelnour et al, (2023) who reported that rabbits under high ambient temperatures decreased T 3 as a result of PSO increase in the diets. The present results agree with those accomplished by Al-Dabbas et al, (2010) who recommend that PSO raises the release of digestive enzymes and improves digestion products through the improvement of the liver enzymes poly-carboxylic acids, phosphate salts, fiber, and proteins digestive.…”
Section: Plasma Hormones and Digestive Enzymesmentioning
confidence: 86%
See 1 more Smart Citation
“…Regarding PSO Ragab et al, (2013b) reported that the concentrations of thyroxin (T 4 ) and triiodothyronine (T 3 ) hormones were higher in groups supplemented by PSO in rabbits which might be related to vitamin E and a phenolic compound found in PSO which has antioxidant properties by removing free radicals and inhibiting fat peroxidation and thus preserving the cell membrane of thyroid gland. Contradicted results were reported by Abdelnour et al, (2023) who reported that rabbits under high ambient temperatures decreased T 3 as a result of PSO increase in the diets. The present results agree with those accomplished by Al-Dabbas et al, (2010) who recommend that PSO raises the release of digestive enzymes and improves digestion products through the improvement of the liver enzymes poly-carboxylic acids, phosphate salts, fiber, and proteins digestive.…”
Section: Plasma Hormones and Digestive Enzymesmentioning
confidence: 86%
“…Regarding PSO, our results are in harmony with those obtained by Negm (2018) supplementation with pumpkin significantly increased IgG and IgM levels. This was explained by the fact that it contains many antioxidants that protect the body and increase its immunity (Abdelnour et al, 2023).…”
Section: Immunological and Antioxidant Statusmentioning
confidence: 99%
“…Additionally, in rabbits exposed to HS conditions, Ragab et al [28] noted that an oral dose of Maca extract at 400 mg/kg BW/d improved the litter size, litter weights at 7, 14, 21, and 28 d, final BW, carcass characteristics (weights of dressing, thigh, trunk, liver, heart, and spleen), blood biochemical constituents (increased plasma levels of total protein, albumin, total bilirubin, and LDL-cholesterol, but decreased plasma contents of glucose, triglycerides, total cholesterol LDL-cholesterol, VLDL-cholesterol, uric acid, AST, and ALT), hormone profile (increased serum estrogen and progesterone concentration, while, cortisol concentration was reduced), antioxidative status (serum TAC concentration), and reproductive efficiency. Abdelnour et al [60] elucidated that the dietary supplementation of pumpkin seed essential oil (2 mL/kg diet) improved the growth performance (live BW, FI, BWG, and FCR), serum biochemical parameters (increased serum levels of total protein, albumin, and globulin, while lowering plasma total bilirubin, ALT, AST, creatinine, uric acid, glucose, cortisol, T 3 , and corticosterone concentrations) and anti-inflammation agent (exhibiting negative caspase-3 immunoreactivity surrounding portal tract) in growing rabbits under HS conditions. Jimoh et al [139] revealed that herbal supplements (10% Phyllanthus or 10% Mistletoe) enhanced semen quality traits (sperm concentration, motility, spermatozoa kinetics, and viability), reduced seminal lipid peroxidation, reduced serum corticosterone concentration and elevated serum concentrations of T 3 , LH, FSH, and testosterone in rabbits' bucks reared under HS conditions.…”
Section: Gingermentioning
confidence: 99%
“…Dietary Zn supplementation was proven to benefit the growth performance of fattening rabbits under HS conditions [16,111,112]. Under HS conditions, the dietary inclusion of ZnO (100 mg/kg; [112]) or nano-Zn (20,40,60, and 80 mg/kg; [16]) improved BW, BWG, FI, and FCR in growing rabbits. Similarly, Kamel et al [111] observed that different dietary Zn sources (50 mg ZnO/kg diet or 30 mg nano-Zn/kg diet) enhanced the final BW, BWG, and FCR in growing rabbits who suffered from HS.…”
Section: Zincmentioning
confidence: 99%
“…Nutraceuticals are natural chemical substances that have a good impact on animal physiological and productive characteristics, and they can be divided into plant nutraceuticals such as medicinal herbs and animal nutraceuticals such as bee products, as well as nutraceutical enzymes such as xylanase (Figure 1). Nutraceutical plant products including herb, vegetable, and fruit seeds/leaves/roots belong to the most frequently used nutraceuticals in livestock farms and are recently gaining popularity in rabbit farms because of their nutritional value and therapeutic properties (Table 1) [7][8][9][10][11][12][13][14][15][16][17]. They can be added to rabbit diets, as a natural antioxidant and immunological stimulant, to improve rabbit growth performance and health [18].…”
Section: Introductionmentioning
confidence: 99%